Synthesis and properties of photosensitive organic and hybrid (inorganic-organic) polymer materials containing chromophoric diazene moiety - Janik, R.; Kucharski, S. (Polimery, 2022)
Two methods of the synthesis of new photosensitive methacrylate polymers (PM) or hybrid polymer materials (PH) containing chromophoric diazene moieties of structures described by general Formulas (I), (II) or (III) were presented. The first one (Scheme A) was based on radical polymerization of chromophoric methacrylate monomer (MM) or copolymerization of this monomer with a non-chromophoric MM in solution. An alternative way to get the title polymers was modification of non-chromophoric polymers by coupling reaction of diazonium salts with dialkylaminophenyl group present in the side chain of the polymers (Scheme B). The yield of the synthesis of chromophoric PM was above 70 %, their number average molecular weight was in the range 3400-23000 and polydispersity was 1.1-3.0. All PM obtained (homo-, co- and terpolymers) were able to form transparent photosensitive films on glass substrates. The photosensitive PH materials (XV) were obtained via sol-gel process. The first step of the process was reaction of the free OH groups containing monomers (IV) (Scheme A) or co- and terpolymes PH [(X), R5 or R6 = CH2CH2OH; Scheme A] with 3-(triethoxysilyl)propyl isocyanate (ICTESP) followed by co-hydrolysis and condensation reaction of the resulting carbamate with tetraethoxysilane. The sol obtained was deposited onto glass plates and hardened to transparent glassy film at ca. 120 oC. The chromophoric methacrylate polymers showed reverse trans-cis isomerization [reaction (5); Fig. 1] in solutions and in thin films under illumination with light. The course of isomerization was dependent on the kind of material containing the chromophore moiety and reaction environment (solution, film). The organic and hybrid polymer glass showed ability to form holographic grating on the films in two beam coupling arrangement with using green laser (532 nm) use. The grating formation was reversible at relatively short illumination period but relatively stable when prolonged beam interference caused thickness gradient in the film. Both types of the gratings could be used in holographic data recording. Detail characteristics of PM and PH obtained (chemicals structure, yield of synthesis, values of Mn, Mw/Mn, Tg as well as parameters describing trans"cis isomerization) are given in Table 1.